2018
DOI: 10.1097/tp.0000000000002198
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Solid Organ Transplantation in Telomeropathy: Case Series and Literature Review

Abstract: To our knowledge, this is the first report of multiple solid organ transplantation in documented telomeropathy. These cases highlight current difficulties of timely diagnosis, therapeutic approach, and postoperative complications in telomeropathy patients in whom several organs are affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…In turn, the demand for solid organ transplants is expected to increase. To date, lung transplantation has been performed mainly for pulmonary fibrosis, with considerably favorable outcomes in adult patients with DC, unlike outcomes of LT 8,10 . As evidenced in the present case by the rapid deterioration of liver function after several interventions and sepsis, persisting hypoxemia requiring intensive care after LT can irreversibly damage the transplanted liver.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In turn, the demand for solid organ transplants is expected to increase. To date, lung transplantation has been performed mainly for pulmonary fibrosis, with considerably favorable outcomes in adult patients with DC, unlike outcomes of LT 8,10 . As evidenced in the present case by the rapid deterioration of liver function after several interventions and sepsis, persisting hypoxemia requiring intensive care after LT can irreversibly damage the transplanted liver.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, lung transplantations and LTs have been performed in patients with DC with pulmonary fibrosis and chronic liver disease, respectively 5‐9 . It has been reported that some patients with telomeropathies require multiple solid organ transplantations 10 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, to our knowledge, this is only the second case of combined lung and liver transplantation, which was performed after careful risk assessment of this procedure in a 52-yearold patient with associated bone marrow and bone disease. (6) The decision to perform combined lung and liver transplantation was driven mainly by the increased risk of postoperative liver decompensation linked to significant portal hypertension. Moreover, concomitant hepatopulmonary syndrome represented an additional argument for combined transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in TERC or TERT are found in approximately 20 and 3% of familial and sporadic IPF cases, respectively, whereas TERC or TERT mutations are very rare in the general population. [139][140][141][142][143] Telomerase dysfunction leads to premature telomere shortening, cellular senescence, and apoptosis. Also, this may be the reason why these patients are more prone to cytomegalovirus infections.…”
Section: Underlying Genetic Disorders Telomeropathymentioning
confidence: 99%
“…Bone marrow failure is the most frequent extrapulmonary manifestation, and is often first detected as isolated thrombocytopenia, with a hypocellular bone marrow. 139,[141][142][143] Data on clinical outcomes of lung transplant patients with underlying telomeropathy are scarce, but this group of patients tends to develop recurrent and otherwise unusual complications that reflect the syndromic nature of their disease. Reported survival rates vary substantially, ranging from 33 to 100% after a follow-up of 1.2 up to 3.2 years.…”
Section: Underlying Genetic Disorders Telomeropathymentioning
confidence: 99%